Nilai Moral dalam Film “Budi Pekerti” dan Relevansinya untuk Pembentukan Karakter Siswa - Shalaika, Malika Dhita; Wicaksana, Muhlis Fajar (Universitas Indraprasta PGRI, 2025)
Character education is a crucial pillar in shaping a generation with strong morals and integrity, yet the challenge lies in finding effective methods to convey these values. Film, as a popular medium, holds significant potential for internalizing moral values, but its use in character education for students remains underutilized. This study aims to analyze the moral values embedded in the film Budi Pekerti by Wregas Bhanuteja and their relevance to character building in students. The study employs a narrative approach with qualitative analysis, grounded in Thomas Lickona's theory of character education, which encompasses cognitive, affective, and behavioral moral dimensions. Data were analyzed through an in-depth observation of the storyline, dialogues, and character behaviors in the film. The findings reveal that the film explicitly conveys moral values such as honesty, patience, responsibility, empathy, and tolerance. These values align with the needs of character development in students within the framework of modern education, particularly the Merdeka Curriculum, which emphasizes strengthening the Pancasila student profile. In conclusion, the film Budi Pekerti serves as an alternative educational medium to support character education in students. This study encourages educators to utilize creative media to integrate moral values into the teaching and learning process.